The development of Austrian education with an accent on the legislative development of secondary education - Novakova, Zdenka (e-Pedagogium, 2018)
The presented text is an overview study about historical changes in secondary education and the status of schools in given time stages offering a comprehensive view of the development of secondary education in the context of legislative changes since the beginning of the 19th century. It focuses on transformational activities from the Revolutionary Year of 1848, the political relaxation of the 1960s, followed by a reflection on the status of schools towards the Church, the Marchett's Reform of 1908, which brought significant changes to Austrian secondary education and the subsequent partial reform of education until 1918, including the development of girls' education as a new category in the education system, with an emphasis on legislative adjustments that have a major impact on the key areas with which education faces.The study is a partial output from IGA PdF 2017/036 - History of Education and History of Pedagogy (metanarative function of the history of education in the Czech educational thinking of 20th century, new themes and trends).
Keywords: secondary education; school status; legislation; transformation of education; reform efforts; girls' secondary education